Creating new partnerships: an examination of two collaborative, grant-funded digitization projects - Oleen, Jenny K.; Olsen, Livia M. S. (My University, 2012)
Many agriculture professors are also avid photographers. Throughout their careers, they photograph the unique, the mundane, and the fantastic. Their photographs and slides range from beautiful roses and champion bulls to wheat covered in rust and sickly sows. During their academic years, they use the slides for class lectures, at conferences, and at presentations to the public. Many professors and researchers also collect print materials, amassing huge collections of pamphlets, research reports and books. These items, though old or out of print, often are unique and have great historic value. They document the progress and results of a professor’s research and academic career. What happens to these valuable materials upon a professor’s retirement? Will they languish in a departmental library? Will they be lost in an attic? Will they be discarded? Hopefully not. These materials represent part of that professor’s knowledge, acquired over a lifetime. They are a valuable source of information for future generations. Two grant-funded, collaborative projects, conducted at Kansas State University, endeavored to remedy this problem. The first project involved digitizing natural history publications which are now available on the Internet through the web portal BiodIS (http://biodis.k-state.edu/), Kansas State University's Biodiversity Information System. The second involved digitizing 35 mm slides of grain sorghum (Sorghum bicolor) disease images slides that were originally captured by Dr. Larry Claflin, a plant pathology professor. Dr. Claflin is an internationally recognized expert on grain sorghum diseases and was nearing retirement when he approached the library about preserving approximately 450 grain sorghum disease slides. Both projects were collaborations between librarians and academic faculty.
Keywords: Digital preservation; Biodiversity information system; Digitization; Grain sorghum